Cap Detection Algorithm Based on Pixel Measurement - Zhang, Wei Guo; Li, Li Feng; Zhang, Chao (Applied Mechanics and Materials, 2014)
In order to improve the cap detection efficiency, reduce cost, this paper puts forward a kind of beverage bottle cap detection algorithm based on pixel, the algorithm according to find out the edge line on midperpendicular, left and right edges, and highlight the bottleneck to judge the cap of the four kinds of four steps. In practice, the system monitoring accuracy above 99%, experiments prove that algorithm has a good practicability.